Acute pancreatitis – costs for healthcare and loss of production. (December 2013) - Andersson, Bodil; Appelgren, Björn; Sjödin, Viktor; Ansari, Daniel; Nilsson, Johan; Persson, Ulf; Tingstedt, Bobby; Andersson, Roland
Abstract Objective. Severity of acute pancreatitis (AP) can vary from a mild to a fulminant disease with high morbidity and mortality. Cost analysis has, however, hitherto been sparse. The aim of this study was to calculate the cost of acute pancreatitis, both including hospital costs and costs due to loss of production. Material and methods. All adult patients treated at Skane University Hospital, Lund, during 2009–2010, were included. A severity grading was conducted and cost analysis was performed on an individual basis. Results. Two hundred and fifty-two patients with altogether 307 admissions were identified. Mean age was 60 ± 19 years, and 121 patients (48%) were men. Severe AP (SAP) was diagnosed in 38 patients (12%). Thirteen patients (5%) died. Acute biliary pancreatitis was more costly than alcohol induced AP (p < 0.001). Total costs for treating mild AP (MAP) in patients ≤65 years old was lower (p = 0.001) and costs for SAP was higher (p = 0.024), as compared to older patients. The overall hospital cost and cost for loss of production was per person in mean €5, 100 ± 2, 400 for MAP and €28, 200 ± 38, 100 for SAP (p < 0.001). The costs for treating AP during the two-year-long study period were in mean €9, 762 ± 19, 778 per patient. Extrapolated to a national perspective, the annual financial burden for AP in Sweden would be ∼ €38, 500, 000; corresponding to €4, 100, 000 per million inhabitants. Conclusions. The costs of treating AP are high, especially in severe cases with a long ICU stay. These results highlight the need to optimize care and continue the identification and focus on SAP, in order to try to limit organ failure and infectious complications.